Charge Relays via Dual Carbon‐Actions on Nanostructured BiVO4 for High Performance Photoelectrochemical Water Splitting. (31st January 2022) - Wang, Yuxiang; Chen, Daoming; Zhang, Jingnan; (Jie Tang) Balogun, M.‐Sadeeq; Wang, Pingshan; Tong, Yexiang; Huang, Yongchao
Abstract: Photoelectrochemical water splitting based on nanostructured bismuth vanadate (BiVO4 ) can be a promising strategy to produce low‐cost and green H2 to replace fossil fuels and realize carbon neutrality. Herein, a simple chemical way to realize in situ carbon doping into BiVO4 crystalline structure is designed and obtained carbon‐doped BiVO4, namely C‐BiVO4, can improve the electronic conductivity of BiVO4 . In addition, the introduction of the synthesized carbon quantum dots (CQDs) as a co‐catalyst, immobilizes CQDs onto the C‐BiVO4 nanosheet and acquires the optimized C‐BiVO4 /CQDs heterogeneous structure, which not only boosts light absorption, but also enhances the separation and transfer of the photo‐generated charges. Stemming from the dual carbon actions, the as‐prepared C‐BiVO4 /CQDs photoanode exhibits an excellent photocurrent density of 4.83 mA cm −2 at 1.23 V versus the RHE without the use of any hole scavengers. To assure the practical application of the sensitive photocatalyst, a polyaniline layer is electroplated onto the C‐BiVO4 /CQDs catalyst as a conducting, electroactive, and protective layer to sustain a remarkable long‐term photocurrent density of 2.75 mA cm −2 for 9 hours. This work suggests that the proposed low‐cost, environmentally friendly dual carbon actions can modify photocatalyst and achieve green production of H2 . Abstract : The authors demonstrate that nonmetallic carbon materials can significantly improve the photoelectrochemical water oxidation performance of bismuth vanadate (BiVO4 ). The resulting C‐doped BiVO4 /carbon quantum dots photoanode exhibits excellent photocurrent density of 4.83 mA cm −2 at 1.23 V versus the RHE without any hole scavenger.